DIRECTIONS FOR ENHANCING INVESTMENT CLIMATE ATTRACTIVENESS: INSTITUTIONAL AND FINANCIAL MECHANISMS IN THE CONTEXT OF UZBEKISTAN’S REGIONS - Ulugbek Mukhammadiev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines policy directions for enhancing the attractiveness of the investment climate across Uzbekistan’s regions and analyzes institutional and financial mechanisms that stimulate investment activity. The study systematizes key constraints shaping the regional investment climate—including infrastructure gaps, bureaucratic barriers in land allocation, limited financial-market depth, insufficient coordination in investor guarantees, and regulatory inconsistencies. Using portfolio evidence from Youth Industrial and Entrepreneurship Zones (2022) and indicators on strategic investment projects (2023), the paper discusses the structure of funding sources and risks related to costs and effectiveness. The results suggest that identifying regional ‘driver’ sectors, introducing a rating-based appraisal of investment projects, supporting production infrastructure through credit/subsidy and leasing instruments, strengthening currency–inflation stability, and minimizing undue state interference can improve predictability and investor confidence.